Mitigating Interlanguage Effects in Learning Prepositions through Using Cognitive Linguistic Approach - Aajami, Raghad Fahmi; Gholami, Javad (Journal of Posthumanism, 2025)
This study examines the challenges faced by Iraqi students and the impact of interlanguage when Iraqi learners use prepositions in English as a foreign language, especially interlanguage, via relying on the cognitive linguistic approach (CL). Ninety participants were involved in this experiment and studied English prepositions, which are part of grammar sessions, through CL to enhance their understanding of prepositions. Some English prepositions are analyzed according to CL and its principles to show their multi-meanings and the special relations between entities. Surveys, pre-test, and post-tests were designed as quantitative methods to collect data. This study found that the difficulties are due to the differences in the structural system of the mother tongue and the target language and the use of some prepositions in a single context, which means that the participants are not aware of the multiplicity of their connotations. The study emphasizes the importance of the cognitive linguistic approach in confronting these challenges. The results showed a significant change in participants’ awareness of the influence of the mother tongue on the target language and the importance of the cognitive linguistic approach.